PENGGUNAAN SENYAWA PEKTIN KULIT JERUK SIAM SEBAGAI EDIBLE COATING TERHADAP KUALITAS BUAH STROBERI (Fragaria vesca) SELAMA PENYIMPANAN - Junaidi, Fahmi; Hermavita, Cindi Dwi; Nur Anggaristi, Kirana Titan; Setiawan, Alifianto; Rismaya, Rina (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2024)
The characteristics of siamese oranges have a 30% part in the form of fruit peel which has not been used and discarded, however, siamese peel has pectin content that can be utilized as an edible coating. The purpose of this research is to determine the effect of using pectin compounds of chayote peel as edible coating on the quality of strawberry fruit during the shelf life. The research method was conducted using a 4x4 factorial complete randomized design with factors of chayote peel pectin concentration and storage temperature. The first factor is the concentration of edible coating from pectin which consists of 4 levels, namely 0%, 1%, 2%, and 3%. The second factor is the length of storage, consisting of 4 levels, namely 3, 6, 9 and 12 days of storage at refrigerator temperature (14oC). The variables observed include weight loss, texture, vitamin C content, pH test, total soluble solids and organoleptic (color, taste and appearance). Based on the analysis of variance, the treatment of pectin concentration comparison of siamese orange peel as edible coating on the shelf life of strawberry fruit has a significant effect (p